In vitro effectiveness of Aloe Vera in natura, 0.12% chlorhexidine gel, and 2% chlorhexidine gel against Enterococccus faecalis - Semenoff, Tereza Aparecida Delle Vedove (2008)
Purpose: To compare the antimicrobial effect of Aloe vera in natura gel, 0.12% chlorhexidine gel, and 2% chlorhexidine gel against Enterococcus faecalis. Methods: Forty Petri dishes containing agar blood culture medium were used. Ten paperdisks soaked in sterilized distilled water were placed in the center of ten Petri dishes (negative control). Microorganism strains were seeded on the other 30 Petri dishes, and 10 dishes received one central paper disk soaked in distilled water (positive control). The remaining 20 dishes received 4 disks per dish moistened in the following substances: distilled water; 2% chlorhexidine gel; 0.12% chlorhexidine gel; and Aloe vera in natura gel. After 60h, all groups were analyzed, and the microorganism growth inhibition halos were compared. Results: The results showed statistically significant differences of antimicrobial effect against E. faecalis among the tested substances, in the following descending order: 2% chlorhexidine gel; 0.12% chlorhexidine gel; Aloe vera in natura gel; and distilled water (P < 0.05). Conclusions: Aloe vera in natura gel had lower antimicrobial effect than both concentrations of chlorhexidine tested. Key words: Aloe; chlorhexidine; Enterococcus faecalis; in vitro